The importance of the client in forming marketing policy of communications in the market of hotel services - Pavlenko, I. G. (Видавництво Львівської політехніки, 2014)
A complex of hotel product promotion is reviewed, the distribution of responsive group of consumers in the relationship marketing is characterized; stages, models of behavioral responses of buyers and the formation of communication goals are specified in the article. Розглянуто комплекс просування готельного продукту, охарактеризовано розподіл контактної аудиторії при маркетингу взаємовідносин, зазначено стадії, моделі поведінкових реакцій покупців та формування комунікаційних цілей.
Цінність клієнта при формуванні маркетингової політики комунікацій на ринку готельних послуг
Keywords: hotel; communication; policy; customer; relationship marketing; responsive group of consumers; готель; комунікація; політика; споживач; маркетинг взаємовідносин; контактна аудиторія